Melanonychia. (27th June 2012) - Jefferson, Julie; Rich, Phoebe
Abstract : Melanonychia, or melanin-derived brown-to-black nail pigmentation, is a diagnostic challenge for clinicians. The most serious disease of the nail unit, melanoma, primarily presents with melanonychia. However, melanonychia most often occurs as a result of benign etiologies such as nail matrix melanocytic activation, nail matrix melanocytic hyperplasia, and nail invasion by melanin-producing pathogens. Regrettably, patients with nail apparatus melanoma are often initially misdiagnosed, and due to diagnostic delays of an average of 2 years, melanoma of the nail unit carries a poor prognosis. Having a thorough knowledge of the various causes of melanonychia and using a systematic approach when evaluating brown-to-black nail pigmentation may help prevent misdiagnosis and thereby improve prognosis.